Energy in the early modern home material cultures of domestic energy consumption in Europe, 1450-1850 - Saelens, Wout 1993-; Blondé, Bruno 1964-; Ryckbosch, Wouter 1984- (Themes in Environmental History, 2023)
Energy in the early modern home -- Notes -- References -- Part I: The materiality of energy: Fuels, technologies and practices -- 1. Continuity and change in the search for domestic warmth: Material culture, fuels and practices (France, sixteenth-nineteenth centuries) -- 1.1 Introduction -- 1.2 The use of the fireplace: aspects and problems -- 1.3 'Search for warmth' rather than 'home heating' -- 1.4 The fundamental problem of access to energy -- 1.5 The subtle hierarchy of fuels -- 1.6 The mechanics of change -- 1.7 Conclusion -- Notes -- References -- 2. A Warm Renaissance: Material culture and heating techniques in Venetian artisans' homes (sixteenth-seventeenth centuries) -- 2.1 Introduction -- 2.1.1 Sources -- 2.2 Living with limited resources: society, economy and architecture -- 2.2.1 Social status and economic means -- 2.2.2 Popular housing -- 2.3 Producing and preserving heat -- 2.3.1 Producing energy -- 2.3.2 Producing and using heat -- 2.4 Energy-saving techniques and tricks -- 2.4.1 Maintaining warmth -- 2.4.2 Preserving body warmth: layering clothing -- 2.4.3 Recipes for keeping warm: the books of secrets -- 2.5 Conclusions -- Notes -- References -- 3. Between home and manufacturing. The use of wood and charcoal in early modern Northern Italy: Two case studies -- 3.1 Introduction: aims, topic and methodology -- 3.2 Notes on wood consumption in Bologna and Milan during the eighteenth century: the context -- 3.3 What affected wood prices? -- 3.4 Notes about wood and charcoal consumption in the valleys of Eastern Lombardy -- Notes -- References -- Appendix -- Part II: The cultural life of energy: Comfort, consumer culture and domesticity -- 4. Fireplaces and stoves as icons of comfort -- References.